Implementation of the Cahayaku Method in Learning Al-Qur'an - Ilis Istiqomatunisa; Wido Supraha; Abas Mansur Tamam (al-Afkar, Journal For Islamic Studies, 2023)
This method was developed by a team from the Ummul Quro Foundation in Bogor with the vision: to be a method of learning the Qur'an that is easy to learn and use. The mission of this Cahayaku method is: 1. To develop and prepare materials and methods for learning the Qur'an that can be learned for all ages. 2.Develop and prepare various learning tools to help facilitate learning of the Qur'an.3. Organizing training and certification to standardize reading Al-Qur'an learning materials and methods. The Cahayaku method has characteristics compared to other Al-Qur'an learning methods, namely: 1) A varied and fun learning approach. (There is an SOP for teaching and learning using the Cahayaku method), 2). Using a special CAHAYAKU logo, 3). Motivating and meaningful learning, 4). Growing the spirit of love for the Qur'an, not just 'chasing the target', 5). Based on the formation of character and the spirit of worship, 6). Based juz 30, 7). Referring to experts in the Qur'an (fulfilling the purification requirements), 8). Khotmul-Qur'an based on "appreciative and motivating testing" not "judgement", 9). Building non-individual institutional cooperation with external institutions.